Integration of Critical Thinking in “English for Change” Textbook for Grade XI: Content Analysis - Anastasia Layu; Ariyanti Ariyanti; Abdul Rohman; Arbain Arbain (Inquest Journal, 2025)
This study aims to analyze the integration of Facione's Critical Thinking Framework in the textbook "English for Change" for grade XI of senior high school (SMA/MA). Using a qualitative descriptive content analysis approach, this study examines the frequency and distribution of six critical thinking aspects of Interpretation (INT), Analysis (ANL), Evaluation (EVA), Inference (INF), Explanation (EXP), and Self-Regulation (SRG) in learning materials and learning activities in five textbook units. Data were collected through systematic document analysis guided by Facione's (2015) operational indicators and validated by an expert in the field of English language teaching and critical thinking. The results showed that in Learning Materials, there were 145 occurrences with ANL dominating (44.8%), while EXP and SRG were almost absent (1.4 each), indicating significant imbalance. In Learning Activities, there were 334 occurrences with a much more even distribution across all aspects. These findings indicate that the “English for Change” textbook integrates critical thinking more comprehensively through activities than the learning materials, and the integration of CT in the Explanation and Self-Regulation dimensions in the materials still needs to be strengthened.